Exploiting the predictive power of educated spheroids to detect immune-mediated idiosyncratic drug-induced liver injury: the case of troglitazone - Roux, Salomé; Cherradi, Sara; Duong, Hong Tuan (Frontiers in Pharmacology, 2024)
Idiosyncratic drug-induced liver injury (iDILI) is a major concern in drug development because its occurrence is unpredictable. Presently, iDILI prediction by preclinical models is unsatisfactory. Moreover,is a challenge and cell toxicity was is observed only at concentrations that are much higher than the therapeutic doses, in these preclinical models. Applying a proprietary cell educating technology, we developed a person-dependent spheroid system that contains autologous educated immune cells, that is able to detect iDILI risk at therapeutic concentrations. Integrating this system into a high throughput screening platform will help pharmaceutical companies to accurately detect iDILI risk of new molecules de-risking drug development.